04. ASSESSMENT OF EFFICACY AND SAFETY OF OSIMERTINIB FOR PATIENTS WITH INTRACRANIAL METASTATIC DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (4th August 2020) - Erickson, Anders; Brastianos, Priscilla; Das, Sunit
Abstract: INTRODUCTION: Intracranial metastatic disease (IMD) is a serious and life-altering complication for many patients with cancer. Targeted therapy may address limitations of current treatments as an additional agent to achieve intracranial disease control in some patients with IMD. Osimertinib is a mutant epidermal growth factor receptor (EGFR) inhibitor that can penetrate the blood-brain barrier and inhibit tumor cell survival and proliferation in patients with non-small cell lung cancer (NSCLC) with specific EGFR mutations. The purpose of this study is to assess the efficacy and safety of osimertinib in the management of IMD. METHODS: Studies reporting intracranial outcomes for patients with EGFR-mutant NSCLC and IMD treated with osimertinib were included. Among 271 records identified in MEDLINE and EMBASE, 15 studies fulfilled eligibility criteria. Outcomes were pooled using a random-effects model. Risk of bias was assessed using the Cochrane Risk of Bias tool and modified Newcastle-Ottawa scale. Information extracted included study characteristics, intracranial efficacy measures, and safety measures. Meta-analyses were conducted to pool applicable outcomes. RESULTS: 15 studies reporting on 324 patients were included in the analysis. Combined CNS ORR and CNS DCR were calculated to be 64% (95% CI, 53–76%; n = 195), and 90% (95% CI, 85–93%; n = 246). Risk ratios for CNS ORR and CNS DCR were calculated to be 1.44 (95% CI, 1.06–1.96; n = 52) and 1.13 (95% CI, 0.96–1.33; n = 52). Included studies reported complete intracranial response rates of 7–23%, median best decrease in intracranial lesion size of 40–64%, and grade 3+ adverse event rates of 19–39%. CONCLUSIONS: Findings reported here support a potential role for osimertinib for patients with EGFR-mutant NSCLC and IMD. Clinical decision-makers would benefit from the inclusion of patients with IMD in future trials to identify factors that predict responses to targeted therapy.